POLITIK MULTIKULTURALISME: SEBUAH GERAKAN KEADILAN DAN KESETARAAN - Latif, Muhaemin (JPP (Jurnal Politik Profetik), 2021)
Politics of multiculturalism is an effort to provide a space for the citizens to participate same opportunity in servicing people to fulfill their interests particularly in public spaces. There are two important element that should be considered are justice and equality. The article discusses the politics of multiculturalism as an important discourse in the field of social and politics discipline. Multiculturalism is not only a contested issue which concern on theoretical concept, but more importantly it is strongly associate with the ideology that can change sosial and political inequality particularly regarding diversities. The author employed a qualitative research methodology focusing library research. To obtain data, the author explored a number of references related to multiculturalism which were written by recognized scholars. The data then categorized based on the politics of multiculturalism themes supported by racism materials and culture studies. The author concludes that politics of multiculturalisme should not only regarded as the issue of differences but also it is a celebration of diversities. Politics of multiculturalisme can generate an action which encourages a movement for change in social inequality.